2001
DOI: 10.1097/00005768-200105000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Inspiratory muscle training improves rowing performance

Abstract: . Purpose: To investigate the effects of a period of resistive inspiratory muscle training (IMT) upon rowing performance. Methods: Performance was appraised in 14 female competitive rowers at the commencement and after 11 wk of inspiratory muscle training on a rowing ergometer by using a 6-min all-out effort and a 5000-m trial. IMT consisted of 30 inspiratory efforts twice daily. Each effort required the subject to inspire against a resistance equivalent to 50% peak inspiratory mouth pressure (PI max ) by usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

40
247
9
11

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 257 publications
(307 citation statements)
references
References 28 publications
40
247
9
11
Order By: Relevance
“…After the second, 6-wk intervention with inspiratory-loaded CM training (CM/IM training) combined with the high-intensity interval program, global CM function enhanced further in ICT group, compared to that of their CON counterparts. In contrast there was little further improvement IM function, which is consistent with the plateau of improvement in P 0 that has been shown previously after 4 to 6-wk of IMT (20,28). However, it may also be due to the fact that the volume of IMT was lower, compared to the preceding 4-wk phase of specific IMT.…”
Section: Discussionsupporting
confidence: 89%
“…After the second, 6-wk intervention with inspiratory-loaded CM training (CM/IM training) combined with the high-intensity interval program, global CM function enhanced further in ICT group, compared to that of their CON counterparts. In contrast there was little further improvement IM function, which is consistent with the plateau of improvement in P 0 that has been shown previously after 4 to 6-wk of IMT (20,28). However, it may also be due to the fact that the volume of IMT was lower, compared to the preceding 4-wk phase of specific IMT.…”
Section: Discussionsupporting
confidence: 89%
“…They used also an incentive spirometer and other resources. The great majority of these works are dedicated to training and evaluating the inspiratory muscles [23][24][25][26] . Only 1 study using other modalities of training specific to the aged population was found.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed an improvement in the IP max of subjects undergoing IMT with different resources, periods of time, apparatus, and ways of randomization. 7,9,14,[17][18][19][20][21][22][23][24] Using many methodologies, other authors did not find improvement in the IP max . 9,[25][26][27][28] In subjects with Duchenne muscular dystrophy, the benefits of resisted IMT were found to be few and difficult distinguish from a learning effect.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, most of the studies have not used a placebo group, rendering the findings difficult to interpret. More recent studies have used reliable and externally valid outcome measures (i.e., simulated time-trial performance) in conjunction with a placebo-controlled experimental design, and most (46,55,104,137), but not all (117), findings from such studies indicate that respiratory muscle training has a small but likely significant effect on endurance exercise performance.…”
Section: Overcoming the Respiratory Limitations To Exercisementioning
confidence: 99%